(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The term “Vega” means natural urge, and “Dharana” means suppression, so collectively, the word Vega Dharana means forceful suppression of natural urge. Vegas are naturally created in the body in order to maintain bodily equilibrium. Initiation of urges is a normal body activity through which unwanted and waste body products are expelled from the body. In order to facilitate the elimination of these substances, the body is equipped with Adharniya Vegas, which appears naturally. So it is very important to respond to these urges and not suppress them as and when they appear. In Ayurveda, it is broadly explained how suppression of urges leads to serious illnesses. The suppression of urges cause disturbance in homeostasis and lead to many metabolic disorders. Vega dharana as a Nidana is a unique concept of Ayurveda. Acharya Vagbhatta, in the Astang Hridaya Sutrasthana, stated that the root cause of almost all diseases is Vega udirandharane. In Ayurveda, Vegadharan of Adharniya vega is one of the causative factors of Hridaya roga. Today, cardiovascular disorders are the world’s leading cause of mortality and responsible for one out of every four deaths. The increased incidence of cardiovascular disease (CVD) all over the world is due to faulty diet patterns and lifestyles. Approx eighty percent of premature deaths from CVD are preventable. The role of Ayurveda in the prevention and cure of cardiovascular disease is very systematic and good. It can be helpful in decreasing the incidence of cardiovascular disease.